2019
DOI: 10.3892/etm.2019.8303
|View full text |Cite
|
Sign up to set email alerts
|

Avicularin inhibits cell proliferation and induces cell apoptosis in cutaneous squamous cell carcinoma

Abstract: Avicularin (AL), quercetin-3-α-L-arabinofur anoside, has various pharmacological properties such as anticancer and anti-infective effects. However, the potential molecular mechanism via which AL exerts its anticancer activity is not fully understood. Cutaneous squamous cell carcinoma (CSCC) is the second most common skin cancer, where metastasis has resulted in in effective clinical treatments. The aim of the present in vitro study was to investigate the anticancer effects and underlying mechanism of AL on hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This flavonoid is one of the major components in our samples of the S. crenata extract. Another study has revealed that avicularin suppresses the viability of SCC13 skin squamous cell carcinoma cultured cells, by inducing apoptosis and inhibiting epithelial–mesenchymal transition [ 33 ]. It has been proposed that the mechanism of these effects against SCC13 cells is the modulation of genes related to apoptosis and epithelial–mesenchymal transition, as well as inhibition of the MEK–NF-κB signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…This flavonoid is one of the major components in our samples of the S. crenata extract. Another study has revealed that avicularin suppresses the viability of SCC13 skin squamous cell carcinoma cultured cells, by inducing apoptosis and inhibiting epithelial–mesenchymal transition [ 33 ]. It has been proposed that the mechanism of these effects against SCC13 cells is the modulation of genes related to apoptosis and epithelial–mesenchymal transition, as well as inhibition of the MEK–NF-κB signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, inhibition of RhoA, a small GTPase involved in integrin and cell skeletal signalling, had the opposite effect of all previously discussed drugs and in fact promoted EMT [ 151 ]. Additionally, proof of concept studies using several natural compounds have reported modulation of EMT markers and properties in cSCC cell lines [ 112 , 149 , 152 , 153 ]. However, these studies lack proper validation of their targets, an in-depth assessment of potential off-target activities, and consequently an understanding for the signalling pathways modulated.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al demonstrated that avicularin possesses OH radical scavenging capacities [ 23 ]. Oxidative damage can be reduced and kept to a minimum by reducing hydroxyl radicals, which may, in turn, allow cell growth due to reduced inflammation caused by stress [ 24 ]. Although we did not investigate the effect of avicularin alone in our previous study that reported an increase in inflammatory markers, it may be due to the combined phytochemicals in the K. pinnata extract [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like many of the other polyphenols previously mentioned, avicularin may offer help to type II diabetic patients. Studies have shown that avicularin can decrease the progression of type II diabetes by reducing levels of fasting blood glucose, triglycerides, and low-density lipoprotein cholesterol, improving β-cell function, and suppressing hepatic steatosis [ 24 , 25 ]. Kaempferol, another flavonoid found in K. pinnata , was shown to regulate concentrations of glucose within cells [ 26 ].…”
Section: Discussionmentioning
confidence: 99%